Effect of acarbose and vildagliptin on plasma trimethylamine N-oxide levels in patients with type 2 diabetes mellitus: a 6-month, two-arm randomized controlled trial - Yang, Xinhui; Zhang, Xiuying; Sun, Chen; Zhao, Cuiling; Kong, Xiangshuang; Zhao, Mingming; Ji, Linong; Li, Yufeng (Frontiers in Endocrinology, 2025)
AimWe aimed to assess the effects of acarbose and vildagliptin on levels of plasma trimethylamine N-oxide (TMAO) and its metabolic precursor in overweight and obese patients with type 2 diabetes mellitus and ascertain the correlation between TMAO and characteristics of diabetes.MethodsThis study employed a randomized, controlled, open interventional design and recruited 100 participants who were overweight/obese and newly diagnosed with type 2 diabetes at Pinggu Hospital, Beijing Friendship Hospital, Capital Medical University, between December 2016 and December 2017. Using the sealed envelope method, participants were randomly allocated (1:1) to either the acarbose group (n = 50) or the vildagliptin group (n = 50). Participants received 6 months of treatment with oral glucose-lowering medications, acarbose, or vildagliptin. Anthropometric measurements, including height, weight, waist and hip circumferences, and blood pressure, were recorded at baseline and 3 and 6 months after the intervention. Blood samples were obtained to assess blood glucose, insulin, gut hormones, TMAO, and metabolic precursors. Data analysis focused on intragroup and intergroup variations.ResultsBaseline characteristics, including weight, BMI, waist and hip circumferences, blood glucose, and gut hormone levels, were comparable between the acarbose and vildagliptin groups (all p>0.05). Intragroup analysis indicated a significant decrease in TMAO levels at 6 months compared with baseline (adjusted p<0.05). L-carnitine and γ-butyrobetaine levels significantly increased at 6 months (all adjusted p<0.05), whereas betaine and choline levels remained non-significant throughout the intervention. Intergroup analysis revealed significantly lower TMAO levels in the acarbose group at 6 months (p<0.05), without significant intergroup differences in L-carnitine, γ-butyrobetaine, choline, or betaine levels (all p>0.05). In the acarbose group, positive correlations were observed between changes in TMAO and BMI, waist circumference, postprandial glucose, fasting insulin, fasting C-peptide, and HOMA-IR from baseline to 6 months (p<0.05).ConclusionsBoth acarbose and vildagliptin treatments significantly reduced TMAO levels in newly diagnosed T2DM patients, with a more pronounced reduction observed in the acarbose group. Furthermore, the decline in TMAO levels correlated significantly with improvements in insulin resistance parameters.Clinical trial registrationhttps://clinicaltrials.gov, identifier NCT02999841.